Perennial grasses of different successional stages under various soil water inputs: do they differ in root length density? - Busso, Carlos Alberto; Bolletta, Andrea Ivana (Asociación Interciencia, Venezuela, 2022)
Information about root length density (RLD) on perennial grasses of different successional stages exposed to various soil water inputs is limited. The effects on RLD of different soil water inputs were evaluated in the late-seral Stipa clarazii Ball, the comparatively earlier-seral S. tenuis Phil, and the earlyseral S. gynerioides Phil. Field studies were conducted in 1996 and early 1997, although treatments were imposed since 1995. S. clarazii and S. tenuis are two important palatable perennial tussock grasses in temperate, semiarid rangelands of central Argentina, where S. gynerioides is one of the most abundant, unpalatable perennial grass species. It was hypothesized that 1) S. clarazii and S. tenuis have a lower RLD under irrigated than under rainfed or water stress conditions, 2) S. clarazii has a greater RLD than S. gynerioides and S. tenuis under all water inputs and sampling dates, and 3) the RLD of the three species will vary with sampling date, within each species and soil water level. Results led to reject hypothesis 1 and accept hypotheses 2 and 3. Maintenance of root growth under all water inputs would allow these species a greater soil exploration and resource finding to sustain regrowth in their native, semiarid environments. Also, the study demonstrated that late-seral perennial grasses (S. clarazii) should have a superior competitive ability than earlier seral grasses (S. tenuis and S. gynerioides) because of, at least in part, their greater average RLD under water stress, rainfed and irrigated conditions.